Konvergensi Standar Laporan Keuangan ke Standar Pelaporan Keuangan Internasional, Apa dan Bagaimana - Heri Sukendar W. (Bina Nusantara University, 2009)
This research aims to explain development of the convergence of financial accounting standards under IFRS outline being implemented in Indonesia. In the early part, background of the convergence from Indonesian GAAP to IFRS is discussed, both economically and politically to the latest developments in the convergence to IFRS at the present. Furthermore, it is also described the basic framework of the IFRS, which is the fundamental preparation of financial report under IFRS. At the end, this research will explain the impact of IFRS convergence on accounting and financial reporting systems, the impact of IFRS on business and the differences between IFRS and tax principles.